PENGELOLAAN ALOKASI DANA DESA KEPANJEN KECAMATAN GUMUKMAS JEMBER TAHUN ANGGARAN 2016 - Chichi Nani Icawati (Jurnal Ilmiah Akuntansi Indonesia, 2018)
This study focuses on the implementation of management systems carried out by the implementing teams established in each village. The implementation of accountability principle of the management of the allocation of village funds starts from the planning stage, the implementation of all activities and post activities so that the management of the allocation of village funds is expected to be accountable. This reseacrch is expected to be useful for Jember district government, especially Kepanjen village Gumukmas in an effort to improve accountability of management of fund allocation of village. This research was conducted in the village of Kepanjen Gumukmas Sub district in fiscal year 2016. Data collection methods used in this research are literature study and field study. Then the results of the study are analyzed through descriptive analysis method where this method which aims to collect, arrage, present and analyze the data so that can be obtained a clear picture of the object in the perusal. The data used in this study are primary data and secondary data with research subjects consisting of village government Kepanjen Gumukmas district. Based on the results of research, stage, planning can be seen from the meeting held by the executive team of the allocation of village funds is still less effective, where in the community participation meeting activities are still very low, due to lack of transparency of information submitted to the village community Kepanjen. Keywords: Accountability, Allocation of village funds, Part